Enhanced photocatalytic degradation of sulfamethoxazole by deposition of Au, Ag and Cu metallic nanoparticles on TiO2. Issue 18 (17th September 2018) - Zanella, Rodolfo; Avella, Edwin; Ramírez-Zamora, Rosa María; Castillón-Barraza, Felipe; Durán-Álvarez, Juan C.
ABSTRACT: Mono- (Au, Ag and Cu) and bi-metallic (Au–Ag and Au–Cu) nanoparticles were deposited on TiO2 and tested for the photocatalytic degradation of sulfamethoxazole using either UV-C or simulated sunlight. The optimal loading of metallic nanoparticles was determined as 1.5 wt% for Au and Ag, and 1.0 wt% for Cu. In the case of bi-metallic nanoparticles, only the ratio 1:0.5 wt% for both Au–Ag and Au–Cu was tested. In experiments using UV-C light, the highest degradation performance was found for Ag/TiO2, while bi-metallic nanoparticles supported on TiO2 also showed increased photocatalytic activity compared with unmodified TiO2 . In simulated sunlight irradiation tests, Au/TiO2 showed to be the most efficient material. Complete mineralization of sulfamethoxazole was achieved when surface-modified materials were tested in both UV-C and simulated sunlight experiments. Photolysis was efficient to fully degrade sulfamethoxazole, although mineralization was lower than 10% for both luminic sources. The main by-products of sulfamethoxazole were determined in photolysis and photocatalysis tests using UV-C light, and degradation paths were proposed. By-products showed non-toxicity and low antibiotic activity. Reuse of the catalysts upon three reaction cycles did not result in the loss of activity.